Plasma Glycated Hemoglobin and Sleep Patterns in Local Patients with Type 2 Diabetes Mellitus - Nabeel Nasir; Muhammad Rustam Waseem; Mirza Zeeshan Sikandar; Asim Mumtaz; Syed Imran Ali Shah (Aziz Fatimah Medical and Dental College, 2021)
Objective: To ascertain glycemic control and sleep quality in patients with Type 2 Diabetes Mellitus and compare them with age-matched non-diabetic control subjects. Methodology: In this cross-sectional study, plasma glycated hemoglobin (HbA1c) levels and sleep patterns in diabetic subjects were compared with non-diabetic control subjects. Ethical approval was granted by the institutional ethical review board of Central Park Medical College vide number CPMC/IRB/1728. After taking written informed consent, a total of fifty participants between the ages of 40-60 years were recruited by convenience sampling from the medical outpatient clinic at Central Park Teaching Hospital in 2018. Based on the fasting blood glucose levels, participants were categorized as Group I (diabetic subjects) and Group II (non-diabetic control subjects). Sleep quality was assessed using two validated scales, namely Insomnia Severity Index (ISI) and Epworth Sleepiness Scale (ESS). HbA1c levels were evaluated using standardized blood assays. Independent samples t-test was employed to determine mean differences between the two groups. A p-value of ? 0.05 was considered significant. Results: Mean age of the study participants (n=50) was 49.28±2.34 years. The diabetic subjects had significantly higher HbA1c levels (10.15±2.50 vs. 6.26±1.04; p-value 0.001) and ISI scores (12.64±7.91 vs. 4.68±4.88; p-value 0.000) as compared to non-diabetic control subjects, indicating poorer glycemic control and greater degree of insomnia. Conclusion: Poorly controlled diabetes mellitus as reflected by higher HbA1c levels is associated with increased insomnia.